1987
DOI: 10.1126/science.3039661
|View full text |Cite
|
Sign up to set email alerts
|

The Maize Transposable Element Ds Is Spliced from RNA

Abstract: In some instances, insertion of maize transposable elements into exons does not result in the total loss of enzymatic activity. In other instances, messenger RNAs of wild-type size are encoded by genes known to contain the maize transposable element Dissociation (Ds) in exons. To understand how Ds is processed from RNA, a study was made of transcripts encoded by two alleles of the maize waxy (wx) gene containing Ds insertions in exon sequences. The analysis was carried out in strains where the Ds element could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
54
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 24 publications
2
54
0
Order By: Relevance
“…In addition to these examples, the null Ds alleles wx-B4 and AdhJ-2FJJ encode non-mutantsize Wx or Adhl transcripts (5,32). Surprisingly, molecular cloning and DNA sequence analysis revealed that these leaky and null alleles contain exon insertions and that all, except Adhi-Fm335, contain insertions in translated exons (5,6,24,27,32).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to these examples, the null Ds alleles wx-B4 and AdhJ-2FJJ encode non-mutantsize Wx or Adhl transcripts (5,32). Surprisingly, molecular cloning and DNA sequence analysis revealed that these leaky and null alleles contain exon insertions and that all, except Adhi-Fm335, contain insertions in translated exons (5,6,24,27,32).…”
mentioning
confidence: 99%
“…Certain Dissociation (Ds)-and defective-suppressor-mutator (dSpm)-containing alleles of the maize alcohol dehydrogenase 1 (AdhilFm335), waxy (wx-m9), and bronze (bz-m13, bz-m13CS9) genes display a stable intermediate or nonmutant phenotype in strains in which these elements cannot transpose, that is, in the absence of the autonomous Activator (Ac) or Spm element (16,19,21,24). In addition to these examples, the null Ds alleles wx-B4 and AdhJ-2FJJ encode non-mutantsize Wx or Adhl transcripts (5,32). Surprisingly, molecular cloning and DNA sequence analysis revealed that these leaky and null alleles contain exon insertions and that all, except Adhi-Fm335, contain insertions in translated exons (5,6,24,27,32).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(ii) In the case of a cauliflower mosaic virus strain which contains a mutation resulting in a partial processing of the cauliflower mosaic virus 35S RNA (in the wild-type strain the 35S RNA does not appear to be spliced), it is one of the most A+U-rich RNA regions that is spliced out (18). (iii) Transposable element sequences located in the coding regions of different maize genes are frequently spliced out, partially restoring a wild-type phenotype (21,44,47,51). In most instances, the A+U content of these sequences is high.…”
mentioning
confidence: 99%